Optimization of preliminary grounding system design for AC substation using modified evolutionary particle swarm optimization / Chin Jun Hao - Chin, Jun Hao (2018)
Grounding grid ensures a reliable operation of substation and provides protection to personnel and equipment under faulty condition. In this work, a preliminary grounding system for AC substation is designed based on certain requirements according to the IEEE standard. A modified stochastic optimization technique, known as modified evolutionary particle swarm optimization (MEPSO), was used to optimize the preliminary design of grounding system of an AC substation. The variables were the number of rods, length of the rods, number of parallel columns and number of parallel rows. Comparison of the optimization results between MEPSO and PSO was made to identify a better preliminary grounding design for AC substation. From the results, it was found that MEPSO yields a better optimized design than PSO, which has lower total cost and grid resistance compared to PSO.